Functioning of the sale model equity release in Poland - Buzałek, Przemysław (Journal of Finance and Financial Law, 2019)
The aim of the article is to present the fuctioning of the sale model equity release in Poland. While analyzing lifetime benefits concluded with elderly people the autor noticed that the market of sale model equity release in Poland needs new legal regulations. Current law regulations are not enough to protect the interest of elderly people.